Optimizing estate planning through strategic mutual fund investments: Analysis on evaluating mutual fund performance models for long term investment objectives - Pillarsetti, Vijai; Rao, K. Madhava (Edelweiss Applied Science and Technology, 2024)
Estate planning is a complex and crucial process for transferring assets to beneficiaries. Optimizing this process involves the strategic integration of mutual funds, which offers numerous advantages such as bypassing probate, diversification, and flexibility. This article explores the Mutual fund performance assessment and the factors that influence mutual fund performance are the two overarching topics of this study. Selecting a performance benchmark that strives to effectively represent the fund manager’s stock selection abilities while also accurately reflecting the fund’s investing strategy is crucial. Investors may make more informed choices about which mutual fund schemes are best for them if they have a firm grasp of the fund’s most salient attributes. Addressing this context, this article presents a novel four factor asset pricing model for unconditional performance measures. In addition, this study presents a comparative analysis of various asset pricing models with unconditional performance measures.